Электролитическое формирование никеляна асимметричном переменном токе в магнитном поле - Щур, Н.А.; Шило, А.Е. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
This paper is described same aspects and results of influencing of the magnetic fields and altering asymmetric current on the nickel electroplating. It was found, what magnetic fields with altering current can be used during electrodepositing of nickel coatings with aim of forming controlling programmed properties.